異質網路環境之行動搜尋關鍵技術---總計畫 - 簡榮宏; JAN RONG-HONG (My University, 2008)
網際網路的搜尋(web search)，目前正漸漸轉移到電信服務上，全球知名的電信服務業者相繼加入。然行動搜索(Mobile Search) 受限於手機裝置諸多限制，無法有效的在異質性的行動無線網路環境下運作，急需要整合性的技術。有鑑於此，本計畫的總目標在於設計與研發行動搜尋之應用及網路平台，並針對下列五個研究課題，分五個子計畫執行：1) 車用隨意網路之存取控制與連結機制; 2) 車用隨意網路之資訊整合、散佈、傳輸與群播技術; 3) 行動無線感測網路連結機制之研發; 4) 以感測系統為基礎之整合式室內及室外定位系統;5) 行動搜尋資料淬取與探勘機制。並透過總計畫加以整合。 子計畫一的主要研究目標在於發展VANET網路之存取控制協定(Media Access Control, MAC)及連結機制(Connectivity Support)。分為三個階段:在第一年的計畫中，先針對網路低層的MAC進行設計，我們將基於未來最有可能被廣泛使用的DSRC標準進行發展，以合乎趨勢的走向。接下來，在第二年的研究裡，我們將為高速移動的車輛設計以有效的叢集化及功率指定方法，以減少網路干擾，進而提升流量產出及管理上的效果。基於這些低層的技術及規劃方法後，最後一年，我們將發展上層的路由及配送方法，以可克服VANET網路因高度移動和短距離傳輸所造成間歇性連結特性及其衍伸的延遲問題，達到可靠傳輸的最終目標。 子計畫二主要的研究目標是使資訊在車用隨意網路中能快速、可靠且有效的傳播。而本計畫主要的研究課題為: (1)在車用隨意網路中如何能在特定的時間內與空間中快速整合、散佈、複製和儲存資訊。(2)由於車用隨意網路有容遲網路之特性，我們也將探討TCP在容遲網路中的運作困難以及解決方法，以達成資訊可靠的傳輸。(3)最後則是研究車用隨意網路的群播協定以達成資訊有效的傳播。 子計畫三目標是要提供與維護無線感測網路的連結性。主要的研發主題有二: (1)動態無線感測網路建構與維護，(2)含具電節點之動態無線感測網路建構與維護。第一個研發主題以支援感測網路節點的移動性為目標，開發識別碼分配、繞送以及單一或群體節點漫遊機制，此外為了減少熱點現象所造成的問題，也會發展平衡網路流量的負載平衡機制，同時為了解決節點耗損造成網路失連的情形，也會研發容錯機制。第二個研發主題則以發展具電節點為路由節點的繞送機制為主，以解決熱點傳輸產生的耗電問題，同時也會研發具電節點的容錯遊機制以及具電節點漫遊或以具電節點為路由節點的群體漫遊機制，以維護整個網路的連結性。 子計畫四之目的在於提供隨時隨地可取得準確性高的定位服務，以提供各類網路系統及位置感知服務系統運作所需的位置資訊。我們將透過分析微型感測元件（如：加速度計、角速度計、電子陀螺儀及磁力計等）的量測資料及配合現有的室內及室外定位系統達成下列四個研究成果：(1)以低廉的成本達到改善全球定位系統（GPS）的精確度；（2）改善室內定位系統的精確度；(3)利用無線網路通訊技術，發展團隊導航功能；(4)以個人定位系統為基礎，開發可還原汽車運動軌跡之車輛行進記錄器。 子計畫五的主要的研究目標將提出一個整合性的行動搜尋環境，有鑑於 Web 2.0 有 用得資訊與豐富的網頁知識，我們將結合Web2.0及網路上的社群結構，提供使用者有用的資料，並將研發資料探勘技術，分析使用者的行為模式，用以預測使用者的行為模式，減少手持式裝置的輸入不便。本計畫中，我們主要的研究課題為 (1). 從 Web 2.0 網站進行一資料的重整，將地理物件如餐廳或是景點，進行資料淬取，以整理出結構化之資料形式，提供行動搜尋之內容。 (2).針對 Web 2.0 網站，進行社群探勘，以便提供行動搜尋更為有用且精準的資訊。(3). 研發使用者行為探勘機制，以主動提供資料，將行動搜尋得整體使用效率達到最佳化。 表

The mobile web search technologies have drawn continuing attention in recent years. However, due to the limit capability and recourses, the mobile devices can not perform well in heterogonous networks environment. For this reason, in this project, we intend to investigate key techniques for the mobile search application and network platform, including five subprojects 1) MobiConnectivity; 2) MobiTransporting; 3) MobiSensing; 4) MobiPositioning; 5) MobiSearching. These techniques will be integrated in our main project. In Subproject I, we intend to develop Media Access Control (MAC) and connectivity mechanisms to support the Vehicular Ad-hoc Networks (VANET). It is a three-year project: In the first year, we will design the MAC protocols based on the Dedicated Short Range Communication (DSRC) standard, which is expected to be wildly used in the near future. In the second year, the design issue on clustering and power assignment will be investigated for very high speed vehicle. Based on these grounds, in the last year, we will propose the carry and forward protocols to overcome the long latency due to the intermittent connectivity in vehicular networks. In Subproject II, the objective is to develop the transportation techniques which provide the fast, reliable and efficient information delivery over VANET. The topics of this research include (1) Fast information fusion, dissemination, replication and storage in VANET. (2) Since VANET inherits some characteristics of Delay Tolerance Network (DTN), we will discuss the TCP issues over DTN and our transport layer solution to achieve reliable end-to-end information transportation. (3) Finally, we will design a multicast protocol for VANET to achieve efficient information forwarding. In Subproject III, the goal is to provide and maintain the connectivity of wireless sensor networks (WSNs) for mobile positioning and services. Corresponding research items of this subproject include (1) dynamic WSN configuration and maintenance, and (2) powered–node-aware WSN configuration and maintenance. The first research item consists of four sub-items: mobility-aware ID assignment and routing mechanism, single node and group mobility support, dynamic load balancing scheme and automatic failure recovery. The second research items comprise three sub-items: powered-node-ware router delegation, powered-node-ware path discovery, and powered-node-ware mobility support and failure recovery. In Subproject IV, we would like to use sensors embedded in hand held devices like accelerometers, gyroscopes, magnetometers, etc., to collect movement information. By combining the analysis results of sensor readings and indoor or outdoor positioning systems, we would like to achieve following four objectives: (1) Improve the accuracy of GPS by utilizing low cost sensors; (2) Improve the accuracy of indoor positioning systems; (3) Develop group navigation systems by applying the wireless communication; (4) Based on the technology developed for personal navigation systems, we would like to develop equipments that can record sensor readings such that we can reconstruct the movement of cars. In Subproject V, we intend to develop an intelligent search services for mobile devices. Our primary goals include (1). discover Geo-Entity (referred to Geographical Entity) from a huge Web 2.0 repository. (2). mine popular co-cited communities in a blogspace. (3). develop mining algorithms to mine sequential patterns across multiple attributes for
Key Techniques for Mobile Search over Heterogeneous Networks
Keywords: Web 2; 0; 資料採礦; 車用隨意網路; 專用短距離傳輸; 存取控制協定; 叢集化; 功率指定; 載送及轉送; 容遲網路; 傳輸層; 擁塞控制; 資訊融合; 群播; 無線感測網路; 熱點問題; 漫遊; 容錯; 省電; 全球定位系統; 個人導航系統; 室內定位系統; 計步器; Web 2; 0; community mining and sequential pattern mining; VANET; DSRC; MAC; clustering; power assignment; carry and forward; Wireless Sensor network; mobility; load balancing; fault tolerance; GPS; personal navigation systems; indoor positioning; pedometer; accelerometer; magnetic compass; gyro; walking path tracking